Adsorptive Removal of Cr(VI) from Aqueous Solution on Hydrous Cerium—Zirconium Oxide. Part I: Process Optimization by Response Surface Methodology - C.A. Rivera Corredor; M.Á. Gómez García; I. Dobrosz-Gómez (Adsorption Science & Technology)
Hydrous cerium–zirconium oxide (Ce 0.25 Zr 0.75 O 2 ) was used for Cr(VI) removal by adsorption. The response surface methodology (RSM) was applied as a tool for the optimization of adsorption operational conditions (temperature, pH and adsorbent dose) with the combined effects of the key processing variables on the Cr removal efficiency (%R Cr ). The following conditions were found to be optimal: pH = 2, temperature = 28 °C, adsorbent dose = 4 g l −1 . The %R Cr obtained experimentally (92%) was in agreement with the value predicted by RSM (88%). The adsorption process followed the pseudo-second-order kinetic model and obeyed the Langmuir isotherm model. Thermodynamic parameters (ΔH°, ΔS° and ΔG°) indicated the exothermic and spontaneous nature of adsorption governed by physisorption interactions. Hydrous Ce 0.25 Zr 0.75 O 2 showed high adsorption capacity (25 mg g −1 ), high desorption efficiency (80%), reached adsorption equilibrium quickly (30 minutes) and high chemical stability. The Cr(VI) adsorption on hydrous Ce 0.25 Zr 0.75 O 2 was not completely reversible. The reduction of Cr(VI) to Cr(III) under acidic conditions was also responsible for Cr(VI) removal.